2005
DOI: 10.1103/physrevb.72.224516
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiocalculation of impurity effects in copper oxide materials

Abstract: We describe a method for calculating, within density functional theory, the electronic structure associated with typical defects which substitute for Cu in the CuO 2 planes of high-T c superconducting materials. The focus is primarily on Bi 2 Sr 2 CaCu 2 O 8 , the material on which most STM measurements of impurity resonances in the superconducting state have been performed. The magnitudes of the effective potentials found for Zn, Ni and vacancies on the in-plane Cu sites in this host material are remarkably c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…So far, these theories have been expressed entirely in terms of phenomenological effective hoppings in the Cu tightbinding model. First principles calculations for Zn in BSCCO in the normal state [27] provide some evidence in support of the filter picture, but until recently it was not possible to include both superconductivity and the various atomic wave functions extending into the barrier layers responsible for the filter. Nieminen et al investigated the conductance spectrum in the BSCCO system using an analysis based on atomiclike wave functions [28], and showed that for the homogeneous system it could be decomposed in a series of tunneling paths, as postulated by the earlier crude proposals [25,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, these theories have been expressed entirely in terms of phenomenological effective hoppings in the Cu tightbinding model. First principles calculations for Zn in BSCCO in the normal state [27] provide some evidence in support of the filter picture, but until recently it was not possible to include both superconductivity and the various atomic wave functions extending into the barrier layers responsible for the filter. Nieminen et al investigated the conductance spectrum in the BSCCO system using an analysis based on atomiclike wave functions [28], and showed that for the homogeneous system it could be decomposed in a series of tunneling paths, as postulated by the earlier crude proposals [25,26].…”
mentioning
confidence: 99%
“…1(c).As pointed out in Refs. [25][26][27][28], the problem lies in the consideration of the Cu lattice sites far from the BiO surface. The correct quantity to study is the continuum LDOS ρ(r, Ω 0 ) at the height of the STM tip, which we assume to be at z = 5Å above the BiO surface.…”
mentioning
confidence: 99%
“…Because the screened Coulomb potential due to these defects is very short range [11], such impurities are frequently modeled by pointlike (δ-function) scatterers. The expected form for the suppression of superconductivity in the BCS theory of d-wave superconductors is then identical to the expression given by Abrikosov and Gor'kov [12] for magnetic impurities in s-wave superconductors (see, e.g., Ref.13).…”
mentioning
confidence: 99%
“…On the other hand, the bands and Fermi surface given by LDA agree relatively well with ARPES results on optimally doped BSCCO-2212, with minor exceptions (see below). Furthermore, as argued in [23], we are primarily interested in high-energy, localized impurity states which should be little affected by the strong electronic correlations which renormalize the band states near the Fermi surface.…”
mentioning
confidence: 99%
“…We use the exchange-correlation functional determined by Ceperly and Alder [21] and parameterized by Perdew and Zunger [22]. Details of the application of the method to impurity problems in Bi 2 Sr 2 CaCu 2 O 8 have been given in [23]. It is known that LDA fails to give the correct band structure for cuprates in general, and in particular fails to describe the metallic/insulating character of the parent compounds.…”
mentioning
confidence: 99%